Results of the comprehensive interpretation of well logs in carbonate and siliciclastic rocks – similarities and differences in the case studies of selected formations - Waszkiewicz, Sebastian; Alvarez, Ronal Barcala; Jarzyna, Jadwiga (Geology, Geophysics and Environment, 2019)
This paper was made using geological and well logging data from the Cuban oilfield area and the Polish Carpathian Foredeep gas deposit to compare the interpretation process and underline similarities and differences between data analysis from two reservoir rocks of different lithology. Data from conventional hydrocarbon deposits, i.e. the Mesozoic Cuban carbonate formation and Miocene shaly-sandy sediments were processed and interpreted using Techlog (Schlumberger Co.) software. Selected approaches were used to determine the step by step volume of shale, total and effective porosity, water/hydrocarbon saturation (Quanti) and for the comprehensive interpretation of well logs (Quanti Elan). Brief characteristics of the carbonate and siliciclastic formations were presented to indicate that the interpretation methodology oriented to the determination of petrophysical properties depends strongly on the type of reservoir. Cross-plots were presented for primary mineral composition recognition, determination of m exponent and resistivity of formation water in the Archie equation. Effective intervals for the carbonate reservoir were calculated according to the Cumulative Hydrocarbon Column methodology. Finally, the results of the interpretation of well logs were presented as continuous curves of mineral composition, including shaliness, porosity and hydrocarbon saturation. The conclusions included recommendations for the effective comprehensive interpretation of well logs in the carbonate and siliciclastic reservoirs.